Determinasi Pembiayaan Usaha Mikro Kecil dan Menengah (UMKM) pada Perbankan Syari’ah Indonesia - Hakim, Kurniawati; Yacoub, Yarlina; Bustami, Bustami (Jurnal Ekonomi Daerah (JEDA), 2020)
This study aims to find out what are the factors that influence the portion of financing for micro small and medium enterprises (SMES) in Islamic banking in Indonesia. The samples used are 14 Sharia Commercial Banks, 469 Sharia BUS Commercial Bank Units, 154 Sharia Business Units (UUS) and 102 Islamic People's Financing Bank (BPRS) registered at Bank Indonesia during the period 2010-2018. The form of this research is quantitative descriptive using secondary data. The method used in this study is themethod VECM (Vector Error Correction Model)using the eviews 10 program. The results show that in the short term the BI Rate does not have a significant effect, but in the long term the BI Rate has a significant and positive effect. Economic growth in the short term does not have a significant effect but in the long run the variable of economic growth has a significant and positive effect. exchange rate in the short term has a significant and negative effect in the long run has a significant and positive effect. Third Party Funds, inflation, not performing financing (NPF) in the short term and long term have no significant effect on the portion of MSME financing in Islamic banks in Indonesia.Keywords: SMES Financing, BI Rate, Economic Growth, Exchange Rate, Third Party Funds, Inflation and NPF.